The Influence of Organization Culture and Agile Leadership on Employee Performance - Fahmi Dzulqarnain; Wasiman Wasiman (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
As the technology industry develops rapidly, it is vital that leaders adapt to this change and maintain their position within the marketplace through their workforce opportunities. This will not only allow the organisation to be competitive, but also to attract and retain the best talent. The purpose of this study was to identify what causes employees in the company, Silentmode Sdn Bhd (a Malaysia-based software provider), to perform effectively or ineffectively. To accomplish this, research analysed the relationship between Organisational Culture and Leadership and how both affect employee productivity. A quantitative causal design was utilised to gather data from every employee (census), with a result of 89 valid responses following extensive data cleaning and analysis by Multiple Linear Regressions. The analysis of results showed a significant difference between the two variables; Culture was not statistically significant, which indicates that Culture is viewed as an administrative policy rather than an influence on behaviour. Conversely, Agile Leadership was determined to have a statistically significant positive effect on employee performance, as it focuses on adaptiveness to change in order for the organisation to remain viable through the challenges of today's marketplace. Culture and Leadership together account for 16.4% of the variance in employee performance. Consequently, it was concluded that while Culture provides a foundation for establishing the settings in which employees operate, Agile Leadership is the foundation on which productivity occurs in the technology industry. Therefore, it is recommended that Management place emphasis on continuing to increase and renew the internalisation of Culture while also developing the Agile competency of the leadership team.